What is the basic profile of the person who wishes to work effectively in tourism? - Maria José Lisboa Antunes Nogueira (Instituto Politécnico de Viseu, 2016)
Tourism is one of the biggest industries in the world. English is presently the way to face globalization and to establish a bridge between peoples. A Tourism course should enable its students to become qualified professionals, to be responsible for their work, to develop self-study strategies, without ever forgetting that each one is an individual and has his/her own characteristics. That is why every ESP course should be learner-centered; the world can became a village without every place loosing its singularities. In this article I have made a brief overview of English for Specific Purposes and discussed Needs Analysis. I consider the importance of students possessing soft-skills and I have also presented the most important professional and self-promotion genres, the situational contexts, professional domains for ESP and the special software needs of students of Tourism. I also proposed some basic competences and attitudes the Tourism operator must aim for.